47295
|
1 |
(* Title: HOL/Isar_Examples/Group_Context.thy
|
|
2 |
Author: Makarius
|
|
3 |
*)
|
|
4 |
|
58882
|
5 |
section \<open>Some algebraic identities derived from group axioms -- theory context version\<close>
|
47295
|
6 |
|
|
7 |
theory Group_Context
|
63585
|
8 |
imports Main
|
47295
|
9 |
begin
|
|
10 |
|
58614
|
11 |
text \<open>hypothetical group axiomatization\<close>
|
47295
|
12 |
|
|
13 |
context
|
61797
|
14 |
fixes prod :: "'a \<Rightarrow> 'a \<Rightarrow> 'a" (infixl "\<odot>" 70)
|
47295
|
15 |
and one :: "'a"
|
55656
|
16 |
and inverse :: "'a \<Rightarrow> 'a"
|
61797
|
17 |
assumes assoc: "(x \<odot> y) \<odot> z = x \<odot> (y \<odot> z)"
|
|
18 |
and left_one: "one \<odot> x = x"
|
|
19 |
and left_inverse: "inverse x \<odot> x = one"
|
47295
|
20 |
begin
|
|
21 |
|
58614
|
22 |
text \<open>some consequences\<close>
|
47295
|
23 |
|
61797
|
24 |
lemma right_inverse: "x \<odot> inverse x = one"
|
47295
|
25 |
proof -
|
61797
|
26 |
have "x \<odot> inverse x = one \<odot> (x \<odot> inverse x)"
|
47295
|
27 |
by (simp only: left_one)
|
61797
|
28 |
also have "\<dots> = one \<odot> x \<odot> inverse x"
|
47295
|
29 |
by (simp only: assoc)
|
61797
|
30 |
also have "\<dots> = inverse (inverse x) \<odot> inverse x \<odot> x \<odot> inverse x"
|
47295
|
31 |
by (simp only: left_inverse)
|
61797
|
32 |
also have "\<dots> = inverse (inverse x) \<odot> (inverse x \<odot> x) \<odot> inverse x"
|
47295
|
33 |
by (simp only: assoc)
|
61797
|
34 |
also have "\<dots> = inverse (inverse x) \<odot> one \<odot> inverse x"
|
47295
|
35 |
by (simp only: left_inverse)
|
61797
|
36 |
also have "\<dots> = inverse (inverse x) \<odot> (one \<odot> inverse x)"
|
47295
|
37 |
by (simp only: assoc)
|
61797
|
38 |
also have "\<dots> = inverse (inverse x) \<odot> inverse x"
|
47295
|
39 |
by (simp only: left_one)
|
|
40 |
also have "\<dots> = one"
|
|
41 |
by (simp only: left_inverse)
|
61797
|
42 |
finally show ?thesis .
|
47295
|
43 |
qed
|
|
44 |
|
61797
|
45 |
lemma right_one: "x \<odot> one = x"
|
47295
|
46 |
proof -
|
61797
|
47 |
have "x \<odot> one = x \<odot> (inverse x \<odot> x)"
|
47295
|
48 |
by (simp only: left_inverse)
|
61797
|
49 |
also have "\<dots> = x \<odot> inverse x \<odot> x"
|
47295
|
50 |
by (simp only: assoc)
|
61797
|
51 |
also have "\<dots> = one \<odot> x"
|
47295
|
52 |
by (simp only: right_inverse)
|
|
53 |
also have "\<dots> = x"
|
|
54 |
by (simp only: left_one)
|
61797
|
55 |
finally show ?thesis .
|
47295
|
56 |
qed
|
|
57 |
|
47872
|
58 |
lemma one_equality:
|
61797
|
59 |
assumes eq: "e \<odot> x = x"
|
47872
|
60 |
shows "one = e"
|
47295
|
61 |
proof -
|
61797
|
62 |
have "one = x \<odot> inverse x"
|
47295
|
63 |
by (simp only: right_inverse)
|
61797
|
64 |
also have "\<dots> = (e \<odot> x) \<odot> inverse x"
|
47295
|
65 |
by (simp only: eq)
|
61797
|
66 |
also have "\<dots> = e \<odot> (x \<odot> inverse x)"
|
47295
|
67 |
by (simp only: assoc)
|
61797
|
68 |
also have "\<dots> = e \<odot> one"
|
47295
|
69 |
by (simp only: right_inverse)
|
|
70 |
also have "\<dots> = e"
|
|
71 |
by (simp only: right_one)
|
61797
|
72 |
finally show ?thesis .
|
47295
|
73 |
qed
|
|
74 |
|
47872
|
75 |
lemma inverse_equality:
|
61797
|
76 |
assumes eq: "x' \<odot> x = one"
|
47872
|
77 |
shows "inverse x = x'"
|
47295
|
78 |
proof -
|
61797
|
79 |
have "inverse x = one \<odot> inverse x"
|
47295
|
80 |
by (simp only: left_one)
|
61797
|
81 |
also have "\<dots> = (x' \<odot> x) \<odot> inverse x"
|
47295
|
82 |
by (simp only: eq)
|
61797
|
83 |
also have "\<dots> = x' \<odot> (x \<odot> inverse x)"
|
47295
|
84 |
by (simp only: assoc)
|
61797
|
85 |
also have "\<dots> = x' \<odot> one"
|
47295
|
86 |
by (simp only: right_inverse)
|
|
87 |
also have "\<dots> = x'"
|
|
88 |
by (simp only: right_one)
|
61797
|
89 |
finally show ?thesis .
|
47295
|
90 |
qed
|
|
91 |
|
|
92 |
end
|
|
93 |
|
|
94 |
end
|